Pro Smartphone Cross-Platform Development iPhone, BlackBerry, Windows Mobile, and Android Development and Distribution - Allen, Sarah; Graupera, Vidal; Lundrigan, Lee.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Learn the theory behind cross-platform development, and put the theory into practice with code using the invaluable information presented in this book. With in-depth coverage of development and distribution techniques for iPhone, BlackBerry, Windows Mobile, and Android, you$1 (Bll learn the native approach to working with each of these platforms. With detailed coverage of emerging frameworks like PhoneGap and Rhomobile, you$1 (Bll learn the art of creating applications that will run across all devices. You$1 (Bll also be introduced to the code-signing process and the distribution of applications through the major application stores, including Research In Motion (BlackBerry), Apple, and Microsoft.s
The Smartphone is the New PC -- The Smartphone is the New PC -- Platform Development and Distribution -- iPhone -- Android -- BlackBerry -- Windows Mobile -- Cross-Platform Native Frameworks -- Rhodes -- RhoSync -- PhoneGap -- Titanium Mobile -- HTML Interfaces -- Mobile HTML and CSS -- iWebKit -- Animated UI with jQTouch -- Sencha Touch -- BlackBerry HTML UI.
Keywords: Computer science; Programming languages (Electronic computers).; Computer Science; Programming Languages, Compilers, Interpreters; Electronic books